What do coaches say? A preliminary investigation of coaches’ verbal behaviours - James Gavin; Nicolò Francesco Bernardi; Elizabeth Thomas; Julie Anne Chacra (International Journal of Evidence Based Coaching and Mentoring)
Professional coaching associations advocate for appropriate patterns of verbal interventions by coaches. This investigation portrays what coaches say based on analyses of 48 sets of 3 consecutive coaching sessions obtained from professional coaches. 37 ways in which coaches verbally intervened with clients were sub-grouped into four categories with average frequencies estimated as follows: 20% - active listening; 33% - inquiring; 33% - influencing; 14% - miscellany. Analysis across three sessions argues for consistency in coaching interventions rather than for varied patterns. For the most part, intervention profiles align with guidance from professional coaching associations for effective coaching practice.